High sensitivity curvature sensor based on a double-sphere tapered no-core fiber Mach–Zehnder interferometer. (November 2022) - Zhu, Xiaojun; Pan, Yongquan; Sun, Ang; Sun, Dan; Liu, Wen; Cao, Juan; Zhang, Guoan; Han, Zhanghua; Zou, Li; Liang, Zhipeng; Shi, Yuechun
Highlights: A curvature sensor with high sensitivity is proposed. It combines the characteristics of no core fiber, spherical structure and MMZI. Extremely sensitive to curvature and insensitive to temperature. The curvature sensitivity is up to −224.64 nm/m −1, and the temperature sensitivity is −5.79 pm /℃. Abstract: A micro-fiber Mach–Zehnder interferometer (MMZI) based on a double-sphere tapered no-core fiber (DST-NCF) for curvature sensing is proposed and experimentally demonstrated. The sensor is composed of the DST-NCF sandwiched to two single-mode fibers (SMF). The DST-NCF is tapered from a double-sphere structure which is fused by no-core fiber (NCF). When light passes through the DST-NCF from SMF, higher-order modes will be excited, which will improve the sensing performance of the MMZI. This proposed structure achieves a significant improvement in curvature sensitivity for the first time by combining the characteristics of NCF, spherical format, and MMZI. When the central waist region is 2.07 mm, the maximum curvature sensitivity of the sensor is −224.64 nm/m −1, which is the highest curvature sensitivity in the MZI structure based on the spherical structure or the NCF as we have known. In addition, the maximum temperature sensitivity is −5.79 pm/℃ in the range of 40 ℃ − 90 ℃. It shows that this sensor has the characteristics of being insensitive to temperature and avoids the cross-sensitivity effect between temperature and curvature.